2022
DOI: 10.1111/bjet.13178
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a gamified morphological awareness intervention on students' cognitive, motivational and affective outcomes

Abstract: Purpose: Morphological awareness (MA), the ability to reflect on and manipulate the smallest language units within a word, has been identified as an essential metalinguistic awareness to predict literacy development. In this study, we examine whether an online gamified English MA programme is more effective than physical face‐to‐face instruction in terms of cognitive, motivational and affective learning outcomes. Method: We applied a quasi‐experimental design using a sample of 33 students in an intervention gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
1
13
0
1
Order By: Relevance
“…Based on Supplementary Table 1 , most of these journal articles were published in the last 6 years, which indicates that gamified EFL/ESL instruction is a relatively new field of research. Researchers of the studies reviewed used a variety of digital learning environments, not only including the widely used Kahoot ( Hung, 2017 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Almusharraf, 2021 ; Chen, 2021 ; Ebadi et al, 2021 ), Duolingo ( Bahjet Essa Ahmed, 2016 ; Guaqueta and Castro-Garces, 2018 ; Ajisoko, 2020 ), Moodle ( Barcomb and Cardoso, 2020 ; Ho, 2020 ; Qiao et al, 2022 ), and some gamified English learning APPs used in China like Baicizhan ( Dindar et al, 2021 ) and Shanbay ( Fan and Wang, 2020 ); but also self-designed gamified software or webpage ( Hwang et al, 2017 ; Hung, 2018 ), which indicates that digital gamified tools could play a vital role in EFL/ESL instruction and learning. The publication sources are influential SSCI-indexed or Scopus-indexed journals and to some extent show the characteristics of the combination of modern technology and language learning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Supplementary Table 1 , most of these journal articles were published in the last 6 years, which indicates that gamified EFL/ESL instruction is a relatively new field of research. Researchers of the studies reviewed used a variety of digital learning environments, not only including the widely used Kahoot ( Hung, 2017 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Almusharraf, 2021 ; Chen, 2021 ; Ebadi et al, 2021 ), Duolingo ( Bahjet Essa Ahmed, 2016 ; Guaqueta and Castro-Garces, 2018 ; Ajisoko, 2020 ), Moodle ( Barcomb and Cardoso, 2020 ; Ho, 2020 ; Qiao et al, 2022 ), and some gamified English learning APPs used in China like Baicizhan ( Dindar et al, 2021 ) and Shanbay ( Fan and Wang, 2020 ); but also self-designed gamified software or webpage ( Hwang et al, 2017 ; Hung, 2018 ), which indicates that digital gamified tools could play a vital role in EFL/ESL instruction and learning. The publication sources are influential SSCI-indexed or Scopus-indexed journals and to some extent show the characteristics of the combination of modern technology and language learning.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Supplementary Table 1 , although there were some drawbacks of using gamification, many empirical studies reviewed reported that both students and teachers held a positive attitude toward using gamification in EFL/ESL learning and teaching, because a gamified course system did increase students’ motivation to learn ( Liu and Chu, 2010 ; Hwang et al, 2017 ; Ge, 2018 ; Homer et al, 2018 ; Hung, 2018 ; Sun and Hsieh, 2018 ; Ho, 2020 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Almusharraf, 2021 ; Chen, 2021 ; Kaban and Karadeniz, 2021 ; Qiao et al, 2022 ), stimulate students’ interest and engagement in learning English ( Hung, 2018 ; Kingsley and Grabner-Hagen, 2018 ; Sun and Hsieh, 2018 ; Ho, 2020 ; Zou, 2020 ; Alawadhi and Abu-Ayyash, 2021 ; Wang et al, 2021 ), help to create an authentic language environment ( Wu et al, 2014 ; Mei and Yang, 2019 ), help students to make improvements in English skills performance and competence ( Sandberg et al, 2014 ; Hung, 2017 ; Hwang et al, 2017 ; Sevilla Pavón and Haba Osca, 2017 ; Lam et al, 2018 ; Hashim et al, 2019 ; Hong et al, 2020 ; Zou, 2020 ), foster the habit of self-learning and realize learning autonomy ( Sandberg et al, 2014 ; Rueckert et al, 2020 ), and help students to get better knowledge retention ( Ge, 2018 ; Chen et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason is that the leader board made the students take their decision‐making about challenging tasks more seriously (Haruna et al, 2021; Hew et al, 2016), such as in relation to reading comprehension activities. It enabled students to see ‘what was possible’ by showing them the progress of more advanced students (Bai et al, 2021; Qiao et al, 2022) and motivated students to exert the cognitive effort to climb the leader board or maintain their positions (Ding et al, 2017). Consequently, the students who participated in the mixed gamification tended to tackle not only the easier task but also challenging tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Gamification elements in our gamification application involves systematic levels, ranking students on the leaderboard based on their collection of points, assigning badges to award their achievements, and progress bars showing completed and uncompleted tasks. These game‐like elements provide an enjoyable and motivating environment that motivated students to exert more efforts in completing the tasks (Ding et al, 2018; Qiao et al, 2022; Shortt et al, 2021), and consequently improve students' learning performance. This research extends the finding to a highly under‐researched area (i.e., MA) and advances our understanding of how to design the gamified courses using two theories, namely the instructional theory First Principles of Instruction (Merrill, 2002) and the motivational theory self‐determination theory (Deci & Ryan, 2012).…”
Section: Discussionmentioning
confidence: 99%